Factors that intervene in the nutritional quality of life of the inmates of the penitentiary and prison center of Bucaramanga (Colombia). (@limentech, Ciencia y Tecnología Alimentaria, 2022)
It has been observed, by numerous professionals worldwide, that the population incarcerated in prisons presents a food problem caused by various causes. Based on the above, it was seen the need to carry out a project on said population so that with its results, decision makers generate public policies according to their needs. The main factors that intervene in the nutritional quality of life of the inmates of a National Order Reclusion facility (ERON) in Colombia were evaluated. Direct observation and relational analysis were used between nutritional assessment, food consumed, smoking and sedentary lifestyle, the data was obtained from the historical file of the nutritional diagnosis from 2013 to 2016 in 108 women in a situation of sentences (50% of that population) of the inmates of the Penitentiary and Prison Center of Bucaramanga, the Good Shepherd. It was found that the caloric intake of the established meal allows maintaining the balance between the energy consumed and the energy spent, as long as dailyphysical activity is performed; the consumption of food outside the menu demands an increase in physical exercise. It was determined that more than 50% of the population suffers from overweight and obesity, 69% of the surveyed population has the habit of smoking and more than 50% do not exercise and have a sedentary life, additionally they have a habit of consuming food unhealthy and have cardiovascular risk.
Keywords: foods; habits; inmates; risk